Childhood acute poisoning in a tertiary medical college hospital of Bangladesh - Rashid, MM; Hasan, MA; Chowdhury, FR (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S12-14.The abstract of this article is available on the PubMed website